Proteomic Analysis of Fusarium oxysporum-Induced Mechanism in Grafted Watermelon Seedlings - Zhang, Man; Xu, Jinhua; Ren, Runsheng; Liu, Guang; Yao, Xiefeng; Lou, Lina; Xu, Jian; Yang, Xingping (Frontiers in Plant Science, 2021)
Grafting can improve the resistance of watermelon to soil-borne diseases. But, the molecular mechanism of defense response is not completely understood. Herein, we used a proteomic approach to investigate the molecular basis involved in grafted watermelon leaf defense against Fusarium oxysporum f.sp. niveum (FON) infection. The bottle gourd rootstock-grafted (RG) watermelon seedlings were highly resistant to FON compared to self-grafted (SG) watermelon plants, with disease incidence of 3.4% and 89%, respectively. Meanwhile, grafting significantly induced the activity of pathogenesis-related proteases under FON challenge. Proteins extracted from leaves of RG and SG under FON inoculation were analyzed using two-dimensional gel electrophoresis. Thirty-nine differentially accumulated proteins (DAP) were identified and classified into ten functional groups. Accordingly, protein biosynthetic and stress and defence related proteins play crucial roles in the enhancement of disease resistance of RG watermelon seedlings, compared with that of SG watermelon seedlings. Proteins involved in signal transduction positively regulated the defense process. Carbohydrate and energy metabolism and photosystem contributed to energy production in RG watermelon seedlings under FON infection. The disease resistance of RG watermelon seedlings may also be related to the improved scavenging capacity of ROS. The expression profile of 10 randomly selected proteins was measured using quantitative real-time PCR, among which, seven was consistent with the results of the proteomic analysis. The functional implications of these proteins in regulating grafted watermelon response against Fusarium oxysporum is discussed.